2018
DOI: 10.1038/s41598-018-23262-0
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric Plasma Induces ATP-Dependent Endocytosis of Nanoparticles and Synergistic U373MG Cancer Cell Death

Abstract: Gold nanoparticles (AuNP) have potential as both diagnostic and therapeutic vehicles. However, selective targeting and uptake in cancer cells remains challenging. Cold atmospheric plasma (CAP) can be combined with AuNP to achieve synergistic anti-cancer cytotoxicity. To explore synergistic mechanisms, we demonstrate both rate of AuNP uptake and total amount accumulated in U373MG Glioblastoma multiforme (GBM) cells are significantly increased when exposed to 75 kV CAP generated by dielectric barrier discharge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 48 publications
(65 reference statements)
8
83
0
Order By: Relevance
“…To further elaborate on this hypothesis, the uptake of AuNPs into cells was tracked using Our previous work demonstrated that AuNPs accumulate in lysosomes, with significantly more accumulation in the case of CAP-treated cells, after 24 h incubation using confocal imaging and 3D-image construction 11 . Supplementary Figure S6 demonstrates the colocalisation of AuNPs with early and late endosome respectively, which shows a tendency of AuNPs uptake to enter the periphery region of the cells through endocytosis, then gather at the central zone of the cells via endosome trafficking into lysosomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To further elaborate on this hypothesis, the uptake of AuNPs into cells was tracked using Our previous work demonstrated that AuNPs accumulate in lysosomes, with significantly more accumulation in the case of CAP-treated cells, after 24 h incubation using confocal imaging and 3D-image construction 11 . Supplementary Figure S6 demonstrates the colocalisation of AuNPs with early and late endosome respectively, which shows a tendency of AuNPs uptake to enter the periphery region of the cells through endocytosis, then gather at the central zone of the cells via endosome trafficking into lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomes (green) were also counterstained. We have previously demonstrated that AuNPs accumulate in lysosomes 24 hours after 30 s, 75 kV CAP treatment using confocal imaging and 3D-image construction 11 . We demonstrate here that that AuNPs enter U373MG cells mainly through endocytosis, which can be identified first in early and late endosomes after CAP treatment and eventually accumulate in lysosomes (Supplementary Figure S6).…”
Section: Tracking Aunps In Endosomes and Lysosomes And Effects Of Capmentioning
confidence: 99%
See 3 more Smart Citations